PENGARUH KARAKTERISTIK PERUSAHAAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN RISIKO DALAM LAPORAN KEUANGAN INTERIM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fadly, Boy; Simanjuntak, Elsa (JURNAL MUTIARA AKUNTANSI, 2019)
The purpose of this research is to provide empirical evidence aboutcompany characeristics such as firm size, profitability, leverage, and liquidity, and then corporate governance mechanismsuch as board size, and audit committe that affect corporate risk disclosure in interim financial reports.The statistic method that used to test the hypotheses is multiple regressionanalysis. The population of this research are listed mining firms on IDX in2016-2017. Thirty-nine mining firms listed on IDX in 2016-2017 were chosen assample. To explain the effects between the variables, agency and signallingtheories were used. And then, corporate risk disclosure was measured withcontent analysis method. The results of this research show that only firm size and board sizehave significant positive effect on corporate risk disclosure. In addition, theresults do not support that audit committe and firmcharacteristics attributes (profitability, leverage, and liquidity) have significant effect on corporate risk disclosure in interimfinancial reports.